Diversity and abundance of hymenopteran parasitoids at two different elevations in Redang Island, Besut, Terengganu
A study was conducted to determine the diversity and abundance of hymenopteran parasitoids in two different elevations of the coastal and inland forest of Redang Island, Terengganu. Three Malaise traps were installed for each sampling point in the plot area. The insect samples were collected after seven days and brought to the laboratory for sorting, enumerating, and identifying process from order up to the family level. The abundance of parasitoids collected between two plots was statistically analyzed using T-test analysis and one-way Analysis of Variance (ANOVA) was used to compare the abundance of hymenopteran parasitoids between different families. The insect diversity was analyzed using the Shannon-Weiner Diversity Index (H’). Overall, a total of 13 families of hymenopteran parasitoids comprising 48 individuals were successfully identified. The most abundant families identified was Braconidae with 24 individuals followed by Ichneumonidae with six individuals whilst the lowest families identified with only one individual each were Elasmidae, Mutillidae, Diapriidae, Chalcididae, Eulophidae, Pompilidae, Chrysididae, and Platygastridae. The abundance of hymenopteran parasitoids between plots was not significantly different (p>0.05) which coastal forest recorded 26 individuals whereas 22 individuals in the inland forest. However, the Shannon Wiener Diversity Index (H’) showed that the inland forest had significantly higher diversity with the value of H’=1.58 compared to the coastal forest (H’=1.42). In conclusion, the diversity of hymenopteran parasitoids in the inland forest was higher than coastal forest might be due to the variability of the host and plant variation in the higher land. For the future, vegetation species, distribution, and abiotic factors can be taken into consideration in determining the diversity and abundance of hymenopteran parasitoids in the Redang Island forest.